2004
DOI: 10.1530/rep.1.00389
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidant enzymatic defence systems in sheep corpus luteum throughout pregnancy

Abstract: The activities of copper, zinc-superoxide dismutase (SOD1), manganese SOD (SOD2), glutathione peroxidase (GPX), glutathione reductase (GSSG-R) and glutathione S-transferase (GST) were studied in sheep corpora lutea (CL) obtained on days 15, 40, 60, 80 and 128 of pregnancy. Maintained enzymatic activity of SOD1, SOD2, GPX, GSSG-R and GST were found in the sheep CL throughout pregnancy. Enzymatic activity of SOD1, GPX and GST increased significantly from day 15 to day 40 of pregnancy, and thereafter remained con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…Our finding of a significant increase in SOD2 expression in ovine CL in the late luteal phase agrees with the previous findings that CL SOD2 activity increases from mid luteal to late luteal phase in women (Sugino et al 2000) and sheep (Al-Gubory et al 2005). Moreover, SOD2 expression in CLs of pregnant ewes on days 12, 16 and 20 did not alter, in agreement with the previous findings for SOD2 activity (Al-Gubory et al 2004). SOD2 mRNA is induced in the rat CL by inflammatory cytokines (Sugino et al 1998), which are involved in CL regression (Niswender et al 2000).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding of a significant increase in SOD2 expression in ovine CL in the late luteal phase agrees with the previous findings that CL SOD2 activity increases from mid luteal to late luteal phase in women (Sugino et al 2000) and sheep (Al-Gubory et al 2005). Moreover, SOD2 expression in CLs of pregnant ewes on days 12, 16 and 20 did not alter, in agreement with the previous findings for SOD2 activity (Al-Gubory et al 2004). SOD2 mRNA is induced in the rat CL by inflammatory cytokines (Sugino et al 1998), which are involved in CL regression (Niswender et al 2000).…”
Section: Discussionsupporting
confidence: 93%
“…Increased expression of GSTA1 in CL from day 12 to day 16 of pregnancy (this study) is likely an important mechanism protecting the early developing CL against ROS-mediated cell damage. This agrees with the observations that ovine CL GST activity significantly increases from day 15 to day 40 of pregnancy (Al-Gubory et al 2004).…”
Section: Discussionsupporting
confidence: 93%
“…During normal pregnancy, an increased antioxidant status has been reported [17] . Moreover, it has been proposed that the activities of antioxidant enzymes in the corpus luteum are subject to major changes during early pregnancy, suggesting that the corpus luteum of early pregnancy may be rescued from luteolysis through increasing activities of key antioxidant enzymes or metabolites and inhibition of apoptosis [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that the activities of antioxidant enzymes in the sheep corpus luteum (CL) are subject to major changes during early pregnancy, suggesting that the CL of early pregnancy may be rescued from luteolysis through increasing activities of key antioxidant enzymes and inhibition of apoptosis. Maintained levels of antioxidant enzymes in the CL throughout pregnancy may be linked to reactive oxygen species continuously generated in the steroidogenesis activity of luteal cells, and may be involved in the maintenance of luteal steroidogenic activity, cellular integrity and preventive to oxidative stress, improving pregnancy outcomes [27]. Even though the total antioxidant levels were not significantly different, some changes for single antioxidants such as vitamin E, as well as neuroendocrinology-related CART level [28].…”
Section: Discussionmentioning
confidence: 99%